Norma konstitusi sebagai pengendali implisit dalam sistem demokrasi - Rahmah, Aflia; Maharani, Yusi (Maliki Interdisciplinary Journal, 2025)
Constitutional norms have a strategic role as implicit control in the democratic system, especially in maintaining the balance of power and guaranteeing substantive democratic principles. This research aims to analyze the relevance and role of constitutional norms in facing the challenges of modern democracy through a Systematic Literature Review (SLR) approach. The results show that constitutional norms are not only normative, but also play an important role in responding to the challenges of digitalization, political deviance, and weak constitutional education. E-democracy provides opportunities to expand public participation, but also contains the risk of radicalization that must be anticipated through strengthening digital literacy. Therefore, reactualizing constitutional norms is not enough through legal reform, but also requires systemic strengthening of civic values. With a holistic approach, constitutional norms can become a solid foundation in maintaining an equitable and sustainable democracy.